การประยุกต์ใช้หลักสัปปุริสธรรมในการบริหารองค์การบริหารส่วนตำบล ในเขตอำเภอโพนทอง จังหวัดร้อยเอ็ด - โพดาพล, พิเชษฐ์; โพดาพล, ปรมัตถ์ (วารสารศรีล้านช้างปริทรรศน์; Vol 6 No 2 (2020): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 6 ฉบับที่ 2 (กรกฏาคม - ธันวาคม 2563), 2020)
บทความวิจัยนี้มีวัตถุประสงค์เพื่อ (1) ศึกษาการประยุกต์ใช้หลักสัปปุริสธรรม ในการบริหารองค์การบริหารส่วนตำบลในเขตอำเภอโพนทอง จังหวัดร้อยเอ็ด และ (2) เปรียบเทียบการประยุกต์ใช้หลักสัปปุริสธรรม ในการบริหารองค์การบริหารส่วนตำบลในเขตอำเภอ โพนทอง จังหวัดร้อยเอ็ด จำแนกตามตำแหน่ง และประสบการณ์ทำงาน ประชากร ได้แก่ บุคลากรขององค์การบริหารส่วนตำบลในเขตอำเภอโพนทอง จังหวัดร้อยเอ็ด 9 แห่ง กลุ่มตัวอย่าง ได้จากการกำหนดขนาดกลุ่มตัวอย่างโดยสูตร ทาโร ยามาเน่ (Taro Yamane) ได้จำนวน 134 คน ประกอบด้วย ผู้บริหาร จำนวน 45 คน และพนักงานจำนวน 89 คน ในการวิจัยครั้งนี้ได้ใช้เครื่องมือการวิจัยเป็นแบบสอบถาม ใช้การวิเคราะห์ข้อมูลโดยการหาค่าเฉลี่ย () และส่วนเบี่ยงเบนมาตรฐาน (S.D.) การเปรียบเทียบการประยุกต์ใช้หลักสัปปุริสธรรม ในการบริหารองค์การบริหารส่วนตำบลในเขตอำเภอโพนทอง จังหวัดร้อยเอ็ด วิเคราะห์ข้อมูลจากการใช้สถิติเชิงอนุมาน T – test และ One -Way ANOVA          ผลการวิจัยพบว่า 1. การประยุกต์ใช้หลักสัปปุริสธรรม ในการบริหารองค์การบริหารส่วนตำบลในเขตอำเภอโพนทอง จังหวัดร้อยเอ็ด โดยภาพรวมอยู่ในระดับมาก โดยด้านที่มีการประยุกต์ใช้สูงสุด คือ กาลัญญุตา (รู้จักกาล) รองลงมาคือด้านธัมมัญญุตา (รู้หลักหรือรู้จักเหตุ) และด้านอัตถัญญุตา (รู้ความมุ่งหมายหรือรู้จักผล) ตามลำดับ ด้านที่มีการประยุกต์ใช้ต่ำสุด คือ ด้านมัตตัญญุตา (รู้จักประมาณ) 2. การเปรียบเทียบการประยุกต์ใช้หลักสัปปุริสธรรม ในการบริหารองค์การบริหารส่วนตำบลในเขตอำเภอโพนทอง จังหวัดร้อยเอ็ด จำแนกตามตำแหน่งโดยภาพรวมและรายด้าน พบว่า มีการประยุกต์ใช้หลักสัปปุริสธรรม ในการบริหารแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 โดยผู้บริหารมีการประยุกต์ใช้หลักสัปปุริสธรรมสูงกว่าพนักงาน 3. การเปรียบเทียบการประยุกต์ใช้หลักสัปปุริสธรรม ในการบริหารองค์การบริหารส่วนตำบลในเขตอำเภอโพนทอง จังหวัดร้อยเอ็ด จำแนกประสบการณ์ทำงาน พบว่า มีการประยุกต์ใช้หลักสัปปุริสธรรม ในการบริหารแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 โดยบุคลากรที่มีประสบการณ์การทำงาน 10 ปีขึ้นไป มีการประยุกต์ใช้ผู้บริหารมีการประยุกต์ใช้หลักสัปปุริสธรรมสูงกว่าบุคลากรที่มีประสบการณ์การทำงาน 5 – 10 ปี และ 1 – 5 ปี ตามลำดับ             This research has these objectives: 1. to study application of administrative principles in accordance with the sabburisadhamma to Subdistrict administrative qrganizations, in Phonthong District, Roi Et Province. And 2. To campare application of administrative principles in accordance with the sabburisadhamma to Subdistrict administrative organizations, in Phonthong District, Roi Et Province, classified according to position and experience.   The population was the personnel of 9 places of the Subdistrict Administration Organization in the area of ​​Phon Thong District. Roi Et Province. The sample size was determined by the Taro Yamane formula, consisting of 134 people, consisting of 45 executives and 89 employees. In this research, research tools were used as questionnaires. The data was analyzed by means () and standard deviation (S.D.). Comparison of the application of the Sappurisadhamma principles In the administration of the subdistrict administration organization in the district of Phon Thong District Roi Et Province Data were analyzed using inferential statistics, T - test and One-Way ANAVA.             The results of the research are as follows: 1. Application of the Sappurisadhamma In the administration of the subdistrict administration organization in the district of Phon Thong District Roi Et Province appear that in overall is in a high level, The aspect that has the most application is "Sanyaka" (known as "Time"), followed by Dhamma (Know the principles or know the reason) and the object of wisdom. (Know the purpose or know the result), respectively. The areas with the lowest application are the Matagna. 2. Comparison of the application of the Sappurisadhamma In the administration of the subdistrict administration organization in the district of Phon Thong District Roi Et Province, classified by position, overall and in each aspect, found that the application of the Sappurisadhamma In the administration of statistically significant differences at the level of 0.05, with the executives applying the Sappurisadhamma principles higher than the employees. 3. Comparison. In the administration of the subdistrict administration organization in the district of Phon Thong District Roi Et Province, classifying experience, found that the application of the Sappurisadhamma. In administration were different statistically significant at the level of 0.05, with personnel with 10 years of working experience and higher, with the application of administrators having the application of the Sappurisadhamma principles higher than those with 5-10 working experience years and 1 - 5 years respectively.